Total Mercury in Sediments, Macrophytes, and Fish from a Shallow Steppe Lake in Eastern Austria. Issue 8 (August 2014) - Jirsa, Franz; Pirker, Daniel; Krachler, Regina; Keppler, Bernhard K.
Abstract During summer 2011, samples of sediment, macrophytes, and fish tissues from the shallow, slightly alkaline Lake Neusiedl, Austria, were evaluated for their total Hg content. This is the first report of Hg levels from this lake. Sediments displayed Hg contents between 0.025 and 0.113 μg g−1 dw (dry weight), significantly correlating with the proportion of organic components pointing to a small anthropogenic impact on the lake's Hg content. Hg Levels in plants and fish were unexpectedly high: both investigated submerged plant species, Potamogeton pectinatus and Myriophyllum spicatum, showed mean values of 0.245±0.152 and 0.298±0.115 μg g−1 dw, respectively. Biomagnification was evident when comparing muscle samples of the planktivorous fish species rudd Scardinus erythrophthalmus (n=10, mean=0.084 μg g−1 ww (wet weight)) with the piscivorous perch Perca fluviatilis (n=21, mean=0.184 μg g−1 ww) or pike‐perch Sander lucioperca (n=9, mean=0.205 μg g−1 ww). Significantly lower values were found in the muscle of the piscivorous pike Esox lucius (n=25, mean=0.135 μg g−1 ww), pointing to a specific Hg metabolism of this fish, presumably under the particular physicochemical properties of the lake. Hg Concentrations in fish could pose a risk to piscivorous birds in this protected wetland system.